Examining Community Restaurant Nutrition Environments for Cardiovascular Health: An Assessment of Hispanic Caribbean Restaurants in New York City. (29th May 2020) - Fuster, Melissa; Pouget, Enrique; Sakowitz, Eddie Nelson; Halvey, Kayla; Ray, Krishnendu; Elbel, Brian; Handley, Margaret; Huang, Terry T-K
Abstract: Objectives: Examine the nutrition environment in Hispanic Caribbean (HC) restaurants, and identify restaurant-level factors associated with healthier nutrition restaurant environments. Methods: We adapted the Nutrition Environment Measure Survey for Restaurants (NEMS-R) to HC cuisines and applied the instrument (NEMS-HCR) to a random sample of Cuban, Puerto Rican, and Dominican restaurants in New York City (n = 89). Descriptive and regression analysis examined the associations between the NEMS-HCR score and restaurant characteristics (HC cuisine, restaurant type, and midpoint price). Results: No restaurant offered dishes labeled as healthy and almost none (2%) offered whole grains or fruit. Half of the restaurants (52%) had menus with a large proportion (>75%) of nonfried (NF) main dishes and three-quarters (76%) offered at least one vegetarian option. The most common environmental facilitator to healthy eating was offering reduced portion sizes (21%) and the most common barrier was having salt shakers on tables (40%). NEMS-HCR scores (100-point scale) ranged from 24.1–55.2 (mean = 39.7). Scores varied by cuisine and size category, but not by restaurant type (sit-down vs fast casual). Puerto Rican restaurants had the lowest mean score, compared with Dominican and Cuban restaurants (33.7 ± 6.8, 39.6 ± 6.4, 43.3 ± 6.9, respectively, P  < 0.001). Small restaurants (<22 seats) had significantly lowest scores, compared with large and medium sized (36.7 ± 7.1, 41.3 ± 7.2, 41.6 ± 6.1, respectively, P  < 0.05). Multivariate regression indicated that HC cuisine, restaurant size, and price were significantly associated with the score ( P  < 0.05). Price was found to have a significant quadratic association, where lower scores were found among lower and higher priced restaurants. Conclusions: HC communities present more dietary risk factors than other Hispanic groups. Our study is the first to adapt and apply the NEMS-R to HC restaurants. Restaurants are increasingly important daily sources of food. As interventions targeting individual behavior change have shown limited impact, restaurants represent an important environmental target for health promotion. The assessment showed areas for potential improvements in food offerings and environmental cues to encourage healthful choices in HC restaurants. Funding Sources: CUNY PSC Award and NIH/NHLBI Career Development Award (K01).